Discovery of novel trihybrids based on salicylic acid/isoleucine/N-acylhydrazone: A promising therapeutic opportunity in colorectal cancer - David Preciado, Gustavo Moreno, Wilson Cardona, Andres Felipe Yepes (Journal of Applied Pharmaceutical Science, 2022)
Twelve novel trihybrids bearing salicylic acid/isoleucine/N-acylhydrazone (SA-Ile-NAH) features were designed, synthetized, and evaluated for anti-colorectal cancer (CRC) effects against SW480 human colon adenocarcinoma cells. SA-Ile-NAH hybrids 4a–l were obtained in moderate to excellent yields (54%–94%). Regarding biological results, trihybrids 4a, 4c, 4f, and 4j showed 2- to 8-fold higher cytotoxic activities after 48 hours of exposure than the standard chemotherapeutic 5-fluorouracil (5-FU) (174. 30 ± 19.10), with inhibitory concentration (IC50) values of 20.43 ± 1.88 to 78.15 ± 6.73 μM, respectively. Of those, 2,5-dimethoxy-substituited trihybrid 4j is highlighted for its antiproliferative response with viability below 11% in the low micromolar range after 8 days of treatment, as well as for having no significant toxic effects on nontumorigenic cells (IC50 = 102.40 ± 4.64; IS = 1.31) beyond 48 hours of treatment. Finally, theoretical drug-likeness studies suggest that the promising 4j exhibits optimal biopharmaceutical indices. From a therapeutic perspective, merging key pharmacophoric features of SA-Ile-NAH provides a new medicinal scaffold for developing new chemopreventive agents against CRC.
Keywords: Colorectal cancer, salicylic acid, isoleucine, N-acylhydrazone, cytotoxicity, antiproliferative activity